PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID DENGAN MENITIKBERATKAN ASPEK KEARIFAN LOKAL PADA PEMAHAMAN MATERI IPA KELAS V SD - Muhtar Muhtar; Ana Fitrotun Nisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to explore the characteristics of Android-based Interactive Learning Media that are grounded in Local Wisdom and contain Science subjects for fifth-grade elementary school students. Apart from that, this research also aims to test the validity and practicality of this learning media. The method used in this research is a development method using the ADDIE model (analyze, design, development, implementation, evaluation). The instruments used in this research involve validation and practicality questionnaires. Data was collected through questionnaires with validation test assessment sheets given to 5 experts, with the aim of obtaining validity level data. Apart from that, a small-scale trial was carried out on 6 teachers and 10 students to obtain practical data on the results of media development. The results of the research show that Android-Based Interactive Learning Media Oriented to Local Wisdom with Science Content on Single and Mixed Object Topics for Class V Elementary School has characteristics that can meet differentiated learning needs. This media offers interactivity in text, audio, video and games in the form of applications that can be installed on smartphones and accessed via the web. The validity of this learning media was tested by material experts and media experts, with CVI results in the range of 0.68-1.00, indicating the